KINETIKA FERMENTASI YOGHURT YANG DIPERKAYA UBI JALAR (Ipomea batatas) - Rohula Utami; MA Martina Andriani; Zoraya A Putri (Caraka Tani: Journal of Sustainable Agriculture, 2010)
The purpose of this research is to know the behavior of kinetics fermentation of yoghurt enriched by sweet potato (Ipomea batatas L.). The parameter of kinetics fermentation consist of spesific growth rate (μ), doubling time (td), multiplication degree (n), growth yield constant (Yx/s), product yield constant (Yp/s), and production efficiency of lactic acid. The result indicate that, the number of spesific growth rate (μ), in plain yoghurt is 0.4809/hour, white yoghurt is 0.4510/hour, purple yoghurt 0.5589/hour and orange yoghurt is 0.5880/hour. The number of doubling time (td) in plain yoghurt is 1.4513 hours, white yoghurt is 1.8393 hours, purple yoghurt is 1.3806 hours, and orange yoghurt is 1.2074 hours. The number of multiplication degree (n) in plain yoghurt is 4.9567 times, white yoghurt is 5.5671 times, purple yoghurt is 5.6837 times, and orange yoghurt is 6.0985 times. The number of Growth Yield Constant (Yx/s) and Product Yield Constant Yp/s successively in plain yoghurt is 4,5 x105cfu/mg and 0.082 mg, white yoghurt is 4,2 x105cfu/mg and 0.139 mg, purple yoghurt is 7,5x105 cfu/mg and 0,0712 mg, orange yoghurt is 6,8x105cfu/mg and 0.1046 mg. The number of production efficiency of lactic acid during the fermentation in plain yoghurt is 7,633 %, white yoghurt is 6,458%, purple yoghurt is 4,739% and orange yoghurt is 6,479%.